Matemáticas, pregunta formulada por marielariosaira, hace 6 meses

3. Efectúa :
E =(x+1)(x-1)(x2+1)(x*+1)(x8+1) -x16​

Respuestas a la pregunta

Contestado por bunny47
3

Respuesta:

y= (x + 1)(x - 1)( {x}^{2}  + 1)( {x}^{4}  + 1)( {x}^{8}  + 1) -  {x }^{16}  \\ y = ( {x}^{2}  - 1)( {x}^{2}  + 1)( {x}^{4}  + 1)( {x}^{8}  + 1) -  {x}^{16}  \\ y = ( {x}^{4}   - 1)( {x}^{4}  + 1)( {x}^{8}  + 1) -  {x}^{16}  \\ y = ( {x}^{8}   - 1)( {x}^{8} + 1 ) -  {x}^{16}  \\ y =  {x}^{16}  - 1 -  {x}^{16}  \\ y =  - 1

Formula :

( {x}^{2}  -  {y}^{2} ) = (x - y)(x + y)

Saludos Crack

Sígueme

Otras preguntas